Predicting time to medication access for hematologic malignancies: the impact of an integrated specialty pharmacy and limited distribution drug networks. (3rd September 2019) - Zuckerman, Autumn D.; Peter, Megan E.; Starks, Samuel; Maulis, Matthew; Declerq, Josh; Choi, Leena; Jagasia, Madan
Abstract: Background: Barriers to accessing oral oncolytic therapy include insurance authorization, high copays and limited distribution drug (LDD) networks. In September 2015, a pharmacist joined an outpatient hematology clinic to facilitate timeliness of medications (for which the pharmacy has access) dispensed by Vanderbilt Specialty Pharmacy (VSP). The scope expanded to manage non-VSP medications (LDD) in June 2016. Aims: Compare access time to oral oncolytic therapy between drugs to which VSP has access vs. non-VSP medications, and to test whether patient access time to non-VSP agents reduced after integrating a pharmacist. Methods: We reviewed medical records of adult patients prescribed oral oncolytic therapy by a hematology provider. The primary outcome was the time (in days) from treatment decision to medication shipment, stratified by drug access (VSP vs. non-VSP) and time (Time 1: September 2015–May 2016; Time 2: June 2016–September 2017). Using proportional odds logistic regression, we compared time to medication shipment between VSP and non-VSP drugs, and tested whether time to shipment decreased for non-VSP drugs from Time 1 to Time 2. Results: A total of 367 patients with 410 prescriptions were included: 285 VSP drugs and 125 non-VSP drugs. Median time from treatment decision to shipment was 6 days (IQR: 3–9) for non-VSP and 3 days (IQR: 1–6) for VSP drugs. In Time 1, time from treatment decision to shipment was significantly longer for non-VSP vs. VSP drugs (OR = 6.5, p  < .001). For non-VSP drugs, time to shipment reduced from Time 1 to Time 2 (OR = −0.41, p  = .04). Conclusions: Integrating a pharmacist into clinic significantly shortened time from treatment decision to shipment for non-VSP drugs. However, access to these drugs is still slower than VSP medications as they cannot be fully integrated into clinic workflow. The integrated pharmacist at VSP adds value to patient access and outperforms LDD medications, challenging the value of LDD networks beyond medical economics.